(untitled) (Bangladesh Journal of Neurosurgery, 2020)
Background: Conventional radiography and CT scan failed to reveal the posterior fossa tumors which not accurately show tumors behind bone. MRI is currently recognized as the optimal screening technique for detection of posterior fossa tumors. We tried to compare the MRI findings with the histopathological findings of different types of posterior fossa tumors in pediatric patients. Histopathological reports were regarded as the gold standard. Objective: To assess the diagnostic effectiveness of MRI in detection of posterior cranial fossa tumors in pediatric patients. Methods: This cross sectional study was carried out in the department of Neurosurgery, DMCH, NINS and some private hospitals in Dhaka from March, 2012 to November, 2013. Purposive sampling technique was applied and 34 cases were included in the study. Data were collected by specially designed questionnaire and analysed by SPSS. Results: Out of 34 cases, MRI failed to match with the histopathological diagnosis only in 2 cases. One case was diagnosed as cerebellar astrocytoma by MRI, histopathology proved it brain abscess. In another case, MRI diagnosed as ependymoma but histopathology revealed medulloblastoma. Conclusion: It can be concluded That MRI is accepted as the most effective imaging modality in the diagnosis of paediatric posterior fossa tumors. T1WI, T2WI, FLAIR, axial, sagittal, coronal and T1WI post contrast sequences permit confident diagnosis and localization of the pediatric posterior fossa tumor. Bang. J Neurosurgery 2020; 10(1): 62-66